1999
DOI: 10.1038/sj.bjp.0702687
|View full text |Cite
|
Sign up to set email alerts
|

Mutation at the putative GABAA ion‐channel gate reveals changes in allosteric modulation

Abstract: 1 We have mutated a conserved leucine in the putative membrane-spanning domain to serine in human GABA A b2 and investigated the actions of a number of GABA A agonists, antagonists and modulators on human a1b2DL259Sg2s compared to wild type a1b2g2s GABA A receptors, expressed in Xenopus oocytes. 2 The mutation resulted in smaller maximum currents to g-aminobutyric acid (GABA) compared to a1b2g2s receptors, and large leak currents resulting from spontaneous channel opening. As reported, this mutation signi®cant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 24 publications
(36 reference statements)
11
58
2
Order By: Relevance
“…Spontaneous gating of recombinant GABA A receptors can be enhanced by introducing mutations in the transmembrane 2 domain (Chang et al, 1996;Thompson et al, 1999). In agreement with our findings using native and recombinant GABA A receptors, gabazine has a negligible efficacy relative to bicuculline as an inhibitor of spontaneously active GABA A receptors containing mutations that induce constitutive gating (Chang and Weiss, 1999;Thompson et al, 1999).…”
Section: Gaba-independent Tonic Currents 547supporting
confidence: 79%
“…Spontaneous gating of recombinant GABA A receptors can be enhanced by introducing mutations in the transmembrane 2 domain (Chang et al, 1996;Thompson et al, 1999). In agreement with our findings using native and recombinant GABA A receptors, gabazine has a negligible efficacy relative to bicuculline as an inhibitor of spontaneously active GABA A receptors containing mutations that induce constitutive gating (Chang and Weiss, 1999;Thompson et al, 1999).…”
Section: Gaba-independent Tonic Currents 547supporting
confidence: 79%
“…1A). Weak agonist-induced signals were the result of elevated base-line fluorescence (data not shown), suggesting an increased level of background conductance, which has been reported for some leucine 9Ј mutations in other Cysloop receptors (13,20,(22)(23)(24)(25). The L9ЈF mutant retained a maximal response comparable with that of WT-XFP.…”
Section: Gain-of-function Gating Mutation Increasesmentioning
confidence: 69%
“…A number of studies on both cationselective (nicotinic acetylcholine and serotonin 5-HT 3 ) and anion-selective (GABA and glycine) Cys-loop receptors have demonstrated that mutation of a highly conserved pore-lining residue, leucine 9Ј, to one of several other amino acids can dramatically increase agonist sensitivity through effects on channel gating (13)(14)(15)(16)(17)(18)(19)(20)(21). This gain-of-function effect is evident in the dose-response relation, in which channel activation occurs with lower concentrations of agonist.…”
Section: Gain-of-function Gating Mutation Increasesmentioning
confidence: 99%
“…1). [3][4][5][6][7][8][9][10] Thus, the development of cyclodiene-resistant pests and a worldwide outbreak of fipronil-resistant pests are causing problems. Fipronil is a second generation NCA, but A2′S and A2′G mutations provide a low level of cross-resistance to fipronil.…”
Section: Introductionmentioning
confidence: 99%